Progenitor Cells from the Explanted Heart Generate Immunocompatible Myocardium within the Transplanted Donor Heart - D’Alessandro, David A. (2009)
RATIONALE: Chronic rejection, accelerated coronary atherosclerosis, myocardial infarction and ischemic heart failure determine the unfavorable evolution of the transplanted heart in humans. OBJECTIVE: Here we tested whether the pathological manifestations of the transplanted heart can be corrected partly by a strategy that implements the use of cardiac progenitor cells (CPCs) from the recipient to repopulate the donor heart with immunocompatible cardiomyocytes and coronary vessels. METHODS AND RESULTS: A large number of cardiomyocytes and coronary vessels were created in a rather short period of time from the delivery, engraftment and differentiation of CPCs from the recipient. A proportion of newly formed cardiomyocytes acquired adult characteristics and was integrated structurally and functionally within the transplant. Similarly, the regenerated arteries, arterioles and capillaries were operative and contributed to the oxygenation of the chimeric myocardium. Attenuation in the extent of acute damage by repopulating cardiomyocytes and vessels decreased significantly the magnitude of myocardial scarring preserving partly the integrity of the donor heart. CONCLUSIONS: Our data suggest that tissue regeneration by differentiation of recipient CPCs restored a significant portion of the rejected donor myocardium. Ultimately, immunosuppressive therapy may be only partially required improving quality of life and lifespan of patients with cardiac transplantation.